1998
DOI: 10.1063/1.476191
|View full text |Cite|
|
Sign up to set email alerts
|

Evolution of dissipative processes via a statistical thermodynamic approach. I. Generalized Mori–Heisenberg–Langevin equations

Abstract: Within the scope of a nonequilibrium statistical ensemble formalism we derive a hierarchy of equations of evolution for a set of basic thermo-hydrodynamic variables, which describe the macroscopic nonequilibrium state of a fluid of bosons. This set is composed of the energy density and number density and their fluxes of all order. The resulting equations can be considered as far-reaching generalizations of those in Mori's approach. They involve nonlocality in space and retro-effects ͑i.e. correlations in space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 16 publications
(33 reference statements)
0
5
0
1
Order By: Relevance
“…22 It is shown that the higherorder fluxes keep dying down as time elapses and then we can retain less and less higher-order fluxes in the description of the movement. 20 This is related to Bogoliubov's hierarchy of relaxation times, 23 which, for the case of semiconductors, is described in Refs. 14, 24, and 25.…”
Section: ͑31͒mentioning
confidence: 99%
“…22 It is shown that the higherorder fluxes keep dying down as time elapses and then we can retain less and less higher-order fluxes in the description of the movement. 20 This is related to Bogoliubov's hierarchy of relaxation times, 23 which, for the case of semiconductors, is described in Refs. 14, 24, and 25.…”
Section: ͑31͒mentioning
confidence: 99%
“…Remark 2.9. Indeed, according to information theory, the entropy flux has the form of the sum of several fluxes, each of them multiplied by the thermodynamic conjugate variable of the quantity transported by the flux (such conjugate variable is given by the derivative of the entropy with respect to the variable) [27][28][29]. Note that this is satisfied by the particular expression in equation (2.35).…”
Section: Compatibility With Second Law Of Thermodynamicsmentioning
confidence: 99%
“…Lauck, Vasconcellos and Luzzi [27] developed a nonlinear quantum transport theory for a far from equilibrium many-body system, which is based on nonequilibrium statistical operator method. The hierarchy of generalized evolution equations of dissipative processes in a Bose fluid was derived by Madureira, Vasconcellos and Luzzi [28,29]. The proposed approach may be suitable for a description of the transport coefficients in molecular hydrodynamics, where the coefficients are frequency and wavelength dependent.…”
Section: Introductionmentioning
confidence: 99%